Two new species of Rhagovelia from Colombia (Hemiptera: Heteroptera: Veliidae) with revised keys to the Colombian species in the torquata and robusta groups - Padilla-Gil, Dora N. (Zootaxa, 2012)
Two new species of the Rhagovelia in the torquata and robusta species groups, R. divisoensis sp. n. and R. victoria sp. n.,are described and compared with other allied species. Rhagovelia divisoensis sp. n. constitutes the first record of the torquata group from Colombia. A nomenclatural note is also presented correcting the orthography of R. narinensis.